2006
DOI: 10.1029/2005jd006036
|View full text |Cite
|
Sign up to set email alerts
|

Regional NOx emission strength for the Indian subcontinent and the impact of emissions from India and neighboring countries on regional O3 chemistry

Abstract: [1] This study examines the regional NO x emission strength and influence of external emissions on O 3 -related chemistry over the Indian subcontinent based on a threedimensional chemistry transport model and space-based observations, following up on our earlier work on NO x chemistry over southern Asia. NO x mass and emissions from Global Ozone Monitoring Experiment (GOME) and Model of Atmospheric Transport and Chemistry-Max Planck Institute for Chemistry Version (MATCH-MPIC) over India are compared, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…Concerning the impact of NO x local sources on the upper-tropospheric (500-150 hPa) O 3 , Kunhikrishnan et al (2004) found a maximum of 15 %. Similar results are found by Kunhikrishnan et al (2006) with a 10 to 20 % sensitivity of O 3 to Indian NO x emissions in the middle and upper troposphere (700-200 hPa) over India. From Fig.…”
Section: The O 3 Budgetsupporting
confidence: 75%
See 4 more Smart Citations
“…Concerning the impact of NO x local sources on the upper-tropospheric (500-150 hPa) O 3 , Kunhikrishnan et al (2004) found a maximum of 15 %. Similar results are found by Kunhikrishnan et al (2006) with a 10 to 20 % sensitivity of O 3 to Indian NO x emissions in the middle and upper troposphere (700-200 hPa) over India. From Fig.…”
Section: The O 3 Budgetsupporting
confidence: 75%
“…7g and j. We have therefore an approximate 15 % sensitivity of O 3 to the Indian NO x source in good agreement with Kunhikrishnan et al (2004Kunhikrishnan et al ( , 2006. According to Kunhikrishnan et al (2006), NO x emissions from Indonesia have a non-negligible effect on upper-tropospheric NO x (20-30 %) and O 3 (10-15 %) over India during the ASM period.…”
Section: The O 3 Budgetsupporting
confidence: 63%
See 3 more Smart Citations